PLANNING OF LECTURER QUALITY DEVELOPMENT OF STATE ISLAMIC HIGHER EDUCATION IN ACEH - Husaini, Husaini; Barus, Jumat (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This research was conducted to examine and explain how the planning of lecturer quality development was carried out by the State Islamic Colleges in Aceh. This study used qualitative design with three State Islamic Colleges in Aceh as the objects and locations. The data was obtained through interview and documentation techniques from related officials of the colleges concerned. The results showed that the planning of lecturer quality development of the universities had been set in their strategic plan with three focuses, they are plans to turn lecturers into experts in their fields; plans to develop lecturer expertise; and plans to increase research and community service. The institutions generally have the same commitment to make various good and sufficient plans for the development of the lecturer quality both in terms of capacity and professionalism, however there are two important aspects that determine policy makers in determining their plans.Keywords: Islamic higher education, Aceh, lecturer, competence, quality, planning